2009
DOI: 10.1007/s10532-009-9283-x
|View full text |Cite
|
Sign up to set email alerts
|

Can microbially-generated hydrogen sulfide account for the rates of U(VI) reduction by a sulfate-reducing bacterium?

Abstract: In situ remediation of uranium contaminated soil and groundwater is attractive because a diverse range of microbial and abiotic processes reduce soluble and mobile U(VI) to sparingly soluble and immobile U(IV). Often these processes are linked. Sulfate-reducing bacteria (SRB), for example, enzymatically reduce U(VI) to U(IV), but they also produce hydrogen sulfide that can itself reduce U(VI). This study evaluated the relative importance of these processes for Desulfovibrio aerotolerans, a SRB isolated from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…However, the growth medium in all cases contained trace amounts of ferrous iron, and it was shown previously that the presence of a trace amount of ferrous iron in a 5 mM bicarbonate solution enhances U reduction by hydrogen sulfide. 35 This suggests that hydrogen sulfide is an important and active U reducing agent in mixed and abiotic systems (when amended with 5 mM bicarbonate) and explains the similar level of U immobilization in the +Fe and no-Fe system (Figures 1 and S2).…”
Section: Metabolism and Biofilm Establishment Of D Vulgaris The Resmentioning
confidence: 80%
“…However, the growth medium in all cases contained trace amounts of ferrous iron, and it was shown previously that the presence of a trace amount of ferrous iron in a 5 mM bicarbonate solution enhances U reduction by hydrogen sulfide. 35 This suggests that hydrogen sulfide is an important and active U reducing agent in mixed and abiotic systems (when amended with 5 mM bicarbonate) and explains the similar level of U immobilization in the +Fe and no-Fe system (Figures 1 and S2).…”
Section: Metabolism and Biofilm Establishment Of D Vulgaris The Resmentioning
confidence: 80%
“…The onset of sulfate reduction does not correspond to elevated rates of U(VI) removal, as does the onset of iron reduction. Although the lowest levels of U(VI) were observed at times when dissolved sulfide concentrations were at a maximum, laboratory experiments investigating the kinetics of U(VI) reduction by aqueous sulfide (Hua et al 2006;Boonchayaanant et al 2010) suggest that the mechanism is suppressed at the pH (∼7.5) and alkalinity levels (15-20 mM; [CO 2− 3 ] T ) observed during this phase of Big Rusty. At lower bicarbonate concentrations (≤5 mM), abiotic reduction of U(VI) by aqueous sulfide has been demonstrated, although neither laboratory study investigated the potentially stabilizing effect of dissolved calcium and the formation of Ca-UO 2 -CO 3 ternary complexes.…”
Section: Post-amendment Uranium Dynamics and Alternate U(vi) Removal mentioning
confidence: 99%
“…It was also found that when the medium was buffered with 30 mM carbonate, sulfide did not reduce U(VI) [18]. Recently, other research groups have shown that microbially generated sulfide can reduce uranium in a medium with 15 mM carbonate buffer, and that the lower the carbonate buffer strength, the higher the uranium reduction rate [110].…”
Section: Srb Biofilms On Quartz Surfacementioning
confidence: 98%